BASIC BELIEFS OF THE TRADITIONAL KUKI RELIGION - Changsan, D M (Journal of Dharma, 1992)
The 'Kukis' are one of the major hill-tribes living in the Northeastern part of the Indian sub-continent. They also live in the neighbouring countries, such as, Bangladesh and Myanmar (Burma) in greater number. They are Mongoloid by race, speaking Tibeto-Burman group of language. They are great warriors 'Who carry out successive raids in Bangladesh i , and in Assam. This is most evident in the socalled 'Kuki Rebellion' (1917-1919) against the mighty British empire.